A method for calibrating input (and output) price elasticities - Alba, Michael M.; Briones, Roehlano M. (School of Economics, University of the Philippines, 2009)
We propose theoretically consistent method for calibrating input (and output) price elasticities (of agricultural crops) from a minimal set of given estimates. Our review of production theory suggests three starting points for the exercise: (a) inputs and outputs have to be classified by input nonjointness, (b) production functions may be assumed to be linearly homogenous, and (c) given an n x n (symmetric) matrix of elasticities. Exploring Shephard's Lemma and Euler's Theorem, we work out the method for a cost function with four inputs. We also provide a numerical example involving a 9x9 matrix a multiple-output profit function.